Oral communication - Sebastian, Evelyn L.; Asuncion, Risa P. (Quezon City, Philippines : Maxcor Publishing House Inc., 2014)
The aim of this book is to help students become effective speakers. Oral communication dominates almost all disciplines.
Chapter I. Nature and importance of oral communication -- Chapter II. Verbal and non verbal communication -- Chapter III. Articulation and pronunciation -- Chapter IV. Types of communication -- Chapter V. Listening -- Chapter VI. Types of speeches -- Chapter VII. Preparing Speech -- Chapter VIII. Controlling stage fright -- Chapter IX. Use of Visual Aids.
Includes bibliographical references.
Keywords: PUBLIC SPEAKING -- ORAL COMMUNICATION